Lipoprotein lipase and lipid profiles in plasma and placenta from normal pregnancies compared with patients with intrahepatic cholestasis of pregnancy. (August 2016) - Hao, Z.M.; Ye, Y.F.; Zhang, Y.K.; Yang, S.F.; Ye, X.L.
Abstract: Objective: To analyse lipoprotein lipase (LPL) expression and lipid levels in placenta and plasma of patients with intrahepatic cholestasis of pregnancy (ICP) and normal pregnancies. Methods: This prospective study included 30 patients with ICP and 30 gestational-age-matched pregnancies without any complications. Enzyme-linked immunosorbent assays were used to investigate plasma LPL levels from 28 weeks of gestation, at 4-weekly intervals, to 38 weeks of gestation, and data were assessed longitudinally. Immunohistochemistry, Western blotting and real-time polymerase chain reaction were used to detect placental LPL expression and activity. Placental triglyceride and total cholesterol levels were also analysed. The clinical data related to ICP and lipid profiles were collected retrospectively. Results: Plasma LPL concentration increased with gestational age in both groups, but the increase was limited in the ICP group. Immunohistochemistry revealed LPL staining mainly in syncytiotrophoblasts, and 3, 3′-diamino-benzidine tetrahydrochloride wt% was lower in ICP placenta compared with normal placenta ( p < 0.01). LPL protein and mRNA expression in ICP placenta were significantly lower than in normal placenta ( p < 0.01). LPL activity was not significantly different in both groups. Correlation analysis indicated that the plasma LPL level was negatively associated with the corresponding concentration of total bile acid ( r = −0.57) in the ICP group. Conclusion: Reduced LPL expression in placenta, limited increase in LPL level in maternal plasma, and abnormal lipid profiles were found in patients with ICP. LPL was possibly related to ICP by participating abnormal lipid metabolism.